Decorating Cu2O photocathode with cu/Al bimetallic layer for enhanced photoelectrochemical water splitting. (11th July 2022) - Wang, Pan; Liu, Zhifeng; Han, Changcun; Zou, Yongjin; Tong, Zhengfu; Tan, Baohua
Summary: In this work, we reported a reasonable, simple, and low cost strategy that Cu2 O is decorated with Cu layer and Al layer to realize the improvement of photoelectrochemical (PEC) performance. The results indicate that the Cu/Al layer that has surface plasmon resonance (SPR) effect inherits both properties of which Cu has high conductivity and Al could form thin Al2 O3 layer to hinder Fermi‐level pinning to accelerate the transfer of photoinduced electron‐hole pairs. With the synergistic effect of Cu and Al, Cu/Al/Cu2 O photocathode displays a higher photocurrent density (−2.16 mA/cm 2 at 0 V vs RHE), which is 3.7 times as high as the pure Cu2 O. Thus, loading bimetallic is believed to be an effective strategy and could inspire interest in continuing to explore novel and effective bimetallic catalysts for PEC water splitting. Abstract : Cu/Al/Cu2 O composites for photoelectrochemical water‐splitting was synthesized by a simple method. The Cu/Al layer that has surface plasmon resonance effect inherits both properties of which Cu has high conductivity to accelerate the transfer of photoinduced electron‐hole pairs and Al could form thin Al2 O3 layer to inhibit the recombination of carriers. With the synergistic effect of Cu and Al, Cu/Al/Cu2 O displays a higher PEC performance.